STRATEGI PEMBANGUNAN WILAYAH PERBATASAN PROVINSI KEPULAUAN RIAU - Hendrayady, Agus (Jurnal Ilmu Administrasi Negara (JUAN), 2018)
This is because Riau Islands Province has a very wide border area, there is still a lack of management of natural resources and potential both by the government and the private sector, the handling of the border that is not maximal and sectoral, the level of education and welfare is still low, the lack of security facilities and infrastructure and defense, resulting in weak supervision of various violations of state borders, the lack of integration of programs and activities for the development of border areas.